The effects of business process outsourcing on the quality of catering services in tertiary education industry in Zimbabwe - Paul Mukucha; Tecla Manyika; Garvin Madhuku; Felix Chari (Cogent Business & Management, 2020)
The study sought to determine the effects of Business Process Outsourcing (BPO) on service quality of catering services in the tertiary education industry. Specifically, the outcome variables were food quality, service quality, and the quality of ambience. A statistically determined sample size of 200 was surveyed over a period of one month. The findings indicated that BPO has got statistical significance on all the hypothesised variables. Based on the results attained it was recommended that tertiary education institutions must outsource non-core functions like catering services and concentrate on the provision of education services which are inherently their core business.
Keywords: 650; Business process outsourcing; food quality; quality service; quality of ambience